Human, rat, and mouse metabolism of resveratrol - Yu, CW; Shin, YG; Chow, A; Li, YM; Kosmeder, JW; Lee, YS; Hirschelman, WH; Pezzuto, JM; Mehta, RG; van Breemen, RB (SPRINGER/PLENUM PUBLISHERS, 2002)
Purpose. Resveratrol, a phenolic phytoalexin occurring in grapes, wine, peanuts, and cranberries, has been reported to have anticarcinogenic, antioxidative, phytoestrogenic, and cardioprotective activities. Because little is known about the metabolism of this potentially important compound, the in vitro and in vivo metabolism of transresveratrol were investigated. Methods. The in vitro experiments included incubation with human liver microsomes, human hepatocytes, and rat hepatocytes and the in vivo studies included oral or intraperitoneal administration of resveratrol to rats and mice. Methanol extracts of rat urine, mouse serum, human hepatocytes, rat hepatocytes, and human liver microsomes were analyzed for resveratrol metabolites using reversed- phase highperformance liquid chromatography with on- line ultraviolet-photodiode array detection and mass spectrometric detection (LC-DAD- MS and LC- UV- MS- MS). UV- photodiode array analysis facilitated the identification of cis- and trans- isomers of resveratrol and its metabolites. Negative ion electrospray mass spectrometric analysis provided molecular weight confirmation of resveratrol metabolites and tandem mass spectrometry allowed structural information to be obtained. Results. No resveratrol metabolites were detected in the microsomal incubations, and no phase I metabolites, such as oxidations, reductions, or hydrolyzes, were observed in any samples. However, abundant trans- resveratrol- 3- O- glucuronide and trans- resveratrol- 3-sulfate were identified in rat urine, mouse serum, and incubations with rat and human hepatocytes. Incubation with beta- glucuronidase and sulfatase to release free resveratrol was used to confirm the structures of these conjugates. Only trace amounts of cis- resveratrol were detected, indicating that isomerization was not an important factor in the metabolism and elimination of resveratrol. Conclusion. Our results indicate that trans- resveratrol- 3- O-glucuronide and trans- resveratrol- 3- sulfate are the most abundant metabolites of resveratrol. Virtually no unconjugated resveratrol was detected in urine or serum samples, which might have implications regarding the significance of in vitro studies that used only unconjugated resveratrol.
Keywords: CANCER CHEMOPREVENTIVE ACTIVITY; NATURAL PRODUCT PRESENT; RED-WINE; LIQUID-CHROMATOGRAPHY; PLATELET-AGGREGATION; TRANS-RESVERATROL; MASS-SPECTROMETRY; SMALL-INTESTINE; HUMAN LIVER; GRAPE